2016
DOI: 10.1177/0898264316634571
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Impairment and Anxiety in Older Adults

Abstract: Objective The objective of the study is was investigate the association between hearing impairment and anxiety. Method We conducted a cross-sectional analysis of 1,732 community-based adults aged 76 to 85 years who participated in the Health Aging and Body Composition (ABC) study. Logistic regression models were adjusted for demographic and cardiovascular risk factors. Hearing impairment was defined by the speech-frequency pure tone average. Anxiety was defined as reporting two symptoms of at least “a little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 37 publications
6
64
2
1
Order By: Relevance
“…The association of hearing loss and loneliness has been previously documented in this population, as well as a population aged 18 to 30 years . This is consistent with other research, which has demonstrated an association between hearing loss and depression, social isolation, and anxiety . Pronk et al longitudinally followed loneliness in individuals with hearing loss.…”
Section: Discussionsupporting
confidence: 87%
“…The association of hearing loss and loneliness has been previously documented in this population, as well as a population aged 18 to 30 years . This is consistent with other research, which has demonstrated an association between hearing loss and depression, social isolation, and anxiety . Pronk et al longitudinally followed loneliness in individuals with hearing loss.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it appears that those with HL have a short‐term increase in global psychological distress, but symptoms do not increase over time, possibly indicative of adjustment to HL. Social isolation and sensory deprivation are possible mechanisms underlying the relationship between HL and anxiety . It remains plausible that improvements made in communication skills might partially account for the change observed in psychological symptomatology over time.…”
Section: Discussionmentioning
confidence: 99%
“…Limited cross‐sectional findings indicate that VL is associated with increased risk of anxiety . The relationship between HL and anxiety remains largely unexamined, although a small body of cross‐sectional evidence indicates that older adults with HL are more likely to have anxiety than those without . No studies to date have examined DSL and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well established that anxiety is associated with several chronic physical co-morbidities [1]. Of particular concern are cardiovascular diseases [8], diabetes [9], pulmonary diseases [10], chronic pain [11], infectious diseases such as tuberculosis [12], arthritis [13], edentulism [14], and mainly in older people, visual impairment [15] and hearing problems [16]. Given the increasing prevalence of chronic conditions worldwide [17], a further understanding of the determinants, consequences and management of the comorbidity between anxiety and chronic physical conditions should be a research priority.…”
Section: Introductionmentioning
confidence: 99%